Bearing capacity of composite bucket foundations for offshore wind turbines in silty sand. (1st March 2018) - Jia, Nan; Zhang, Puyang; Liu, Yonggang; Ding, Hongyan
Abstract: A composite bucket foundation (CBF) with seven compartments arranged in a similar honeycomb structure is a relatively new type of structure for offshore wind turbines. Field tests were conducted at a natural water pool with a water depth of 0.4 m in saturated silty sand off the coast of Jiangsu to estimate the horizontal bearing capacity of the CBF. The distribution of soil pressures along the skirt of the CBF with different loading steps helps in explaining the soil-bucket interaction due to the deformation of the CBF. The results show that an increased load will result in a significant increase in the soil pressure in passive zones outside the bucket skirt whereas the soil pressure on the skirt wall in the corresponding active zone remains largely the same. Moreover, the suction pressure inside the separation between the bucket lid and the soil results in a potential bearing capacity with larger loading application, though it will dissipate with further displacement because seepage is observed in the silty sand. The load-displacement relationships obtained using a FEM simulation are almost in same trend with the test results when the elasticity modulus of the soils in the FEM model is set approximately four or five times the compression modulus obtained from the laboratory test. The rotation center of the CBF obtained from the test and FEM results is approximately 0.8 skirt height below the soil surface around the bulkhead along the loading direction under the ultimate horizontal loading. Highlights: The deformation mechanism of the CBF with different loading steps. The rotation center of the CBF is approximately (0.45R, 0.8H) under the ultimate horizontal loading.